Hypermethylation of Genes Detected in Urine from Ghanaian Adults with Bladder Pathology Associated with Schistosoma haematobium Infection - Zhong, Xiaoli; Isharwal, Sumit; Naples, Jean M.; Shiff, Clive; Veltri, Robert W.; Shao, Chunbo; Bosompem, Kwabena M.; Sidransky, David; Hoque, Mohammad O. (PloS one, 2013)
Schistosoma haematobium is associated with chronic bladder damage and may subsequently induce bladder cancer in humans, thus posing a serious threat where the parasite is endemic. Here we evaluated aberrant promoter DNA methylation as a potential biomarker to detect severe bladder damage that is associated with schistosomiasis by analyzing urine specimens. A quantitative methylation-specific PCR (QMSP) assay was used to examine the methylation status of seven genes (RASSF1A, RARβ2, RUNX3, TIMP3, MGMT, P16, ARF) in 57 urine samples obtained from volunteers that include infected and uninfected by S. haematobium from an endemic region. The Fishers Exact Test and Logistic Regression analysis were used to evaluate the methylation status with bladder damage (as assessed by ultrasound examination) in subjects with S. haematobium infection. RASSF1A and TIMP3 were significant to predict severe bladder damage both in univariate (p = 0.015 and 0.023 respectively) and in multivariate (p = 0.022 and 0.032 respectively) logistic regression analysis. Area under the receiver operator characteristic curves (AUC-ROC) for RASSF1A and TIMP3 to predict severe bladder damage were 67.84% and 63.73% respectively. The combined model, which used both RASSF1A and TIMP3 promoter methylation, resulted in significant increase in AUC-ROC compared to that of TIMP3 (77.55% vs. 63.73%.29; p = 0.023). In this pilot study, we showed that aberrant promoter methylation of RASSF1A and TIMP3 are present in urine sediments of patients with severe bladder damage associated with S. haematobium infection and that may be used to develop non-invasive biomarker of S. haematobium exposure and early molecular risk assessmentof neoplastic transformation.